2011
DOI: 10.1016/j.actbio.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and safety of alkoxyethyl cyanoacrylate tissue adhesives

Abstract: Cyanoacrylate glues are easily applied to wounds with good cosmetic results. However, they tend to be brittle and can induce local tissue toxicity. A series of cyanoacrylate monomers with a flexible ether linkage and varying side-chain lengths was synthesized and characterized for potential use as tissue adhesives. The effect of side-chain length on synthesis yield, physical and mechanical properties, formaldehyde generation, cytotoxicity in vitro and biocompatibility in vivo were examined. The incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 41 publications
5
65
0
Order By: Relevance
“…Toxicity of the CA-based synthetic TAs can be reduced by the longer length of their side chain [7][8][9][10], and as a result of much research efforts, alternative TAs such as octyl-2-CA and n-butyl-CA with a longer side chain have been developed and marketed with commercial brand names, Dermabond® (Johnson & Johnson/Ethicon, Somerville, NJ) and Histoacryl® (B. Braun, Melsungen, Germany), respectively [8][9][10][11]. Recently, pre-polymerization process has been demonstrated to allow allyl 2-CA (PACA) to result in a longer chain structure and better for biocompatibility when tested both in vitro and in vivo [12].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity of the CA-based synthetic TAs can be reduced by the longer length of their side chain [7][8][9][10], and as a result of much research efforts, alternative TAs such as octyl-2-CA and n-butyl-CA with a longer side chain have been developed and marketed with commercial brand names, Dermabond® (Johnson & Johnson/Ethicon, Somerville, NJ) and Histoacryl® (B. Braun, Melsungen, Germany), respectively [8][9][10][11]. Recently, pre-polymerization process has been demonstrated to allow allyl 2-CA (PACA) to result in a longer chain structure and better for biocompatibility when tested both in vitro and in vivo [12].…”
Section: Introductionmentioning
confidence: 99%
“…The PAC bond strength was also found to decrease with increasing heating time (Table 1: The cytotoxicity of PAC was determined using a direct-contact culture cell viability test (Table 2). Generally, cytotoxicity decreases with an increase in the length of the intramolecular carbon chains in cyanoacrylates [8] and the cytotoxicity of PAC was therefore expected to decrease with increasing polymerization time. Most samples in this study were found to have a lower cytotoxicity than the control (octyl 2-cyanoacrylate), except the sample that was heat-treated for 0 min (cell viability, 33 ± 1%).…”
Section: Characterization Of Pre-polymerized Allyl 2-cyanoacrylatesmentioning
confidence: 99%
“…However, the application of these polymers has been limited because of their unfavorable mechanical properties and the release of cytotoxic chemicals during their degradation [6,7]. Consequently, these materials are mainly used as biological adhesives in emergencies [2,8]. To overcome the limitations associated with these adhesives, researchers have investigated various cyanoacrylate modifications.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are degradable, but since formaldehyde is a degradation product, their toxicity is an issue. [7,8] For this reason their application is limited to topical skin wound closure. Commercial products are Dermabond 1 and Histoacryl…”
Section: Introductionmentioning
confidence: 99%